Endothelin-1 in idiopathic pulmonary fibrosis. Issue 4 (April 1995) - Uguccioni, M; Pulsatelli, L; Grigolo, B; Facchini, A; Fasano, L; Cinti, C; Fabbri, M; Gasbarrini, G; Meliconi, R
Abstract : AIMS–To evaluate whether endothelin-1 is involved in the pathology of idiopathic pulmonary fibrosis (IPF). METHODS–Plasma endothelin-1 concentrations were evaluated in 37 patients with IPF and 27 normal controls by radioimmunoassay. In addition, expression of endothelin-1 in lung tissue was evaluated in biopsy specimens obtained from four patients with IPF. Three biopsy specimens of normal lung were used as controls. Endothelin-1 immunoreactivity was detected using immunohistochemistry. RESULTS–Elevated endothelin-1 plasma concentrations were found in patients with IPF compared with controls and a positive correlation was found with duration of disease. No significant difference was observed between treated and untreated patients with IPF. Increased endothelin-1 immunoreactivity was found in lungs of three of four patients with IPF. Endothelin-1 positive consisted mainly of small vessel endothelial cells. Some scattered macrophages were also positive. CONCLUSIONS–Elevated plasma concentrations and expression of endothelin-1 in lung tissue are suggestive of increased production of endothelin-1 in at least a proportion of patients with IPF. Consequently, endothelin-1 activity could play a role in the fibrogenic process of the disease.